What, How, and Why? A Comparative Analysis of 12 Goal-Free Evaluations - Brandon W. Youker (The Evaluation Center at Western Michigan University, 2019)
Background: Goal-free evaluation (GFE) is any evaluation in which the evaluator conducts the evaluation without reference to predetermined goals or objectives.     Purpose: The purpose of this study is to examine GFE in actual practice focusing on what GFE is, how it is conducted, and why the evaluators use it.   Setting: Not applicable.   Intervention: Not applicable.   Research Design:  Document analysis. Data Collection and Analysis: The researcher collected data from a non-random sample of 12 cases of GFE found in published and non-published papers, reports, and guidebooks. The researcher analyzed the documents using quantitative and qualitative content analysis.   Findings: The findings suggest that goal-free evaluators consider GFE an outcome evaluation that supplements GBE. These goal-free evaluators typically used an ex post facto evaluation design, non-random sampling of stakeholders, and semi-structured interviewing to collect data. The evaluators described using GFE to improve the evaluand, to find side-effects, and to evaluate highly complex evaluands.